Fostering Pre-Service Teachers’ Creativity through Ethno-STEM Project Based Learning: A Preliminary Study - Ni Made Yeni Suranti; Nurkhaerat Alimuddin; Fitri Puji Astria; Aisa Nikmah Rahmatih (Indonesian Journal of Elementary and Childhood Education, 2025)
This study is a preliminary study that aims to identify the initial conditions of creativity of prospective elementary school teachers in the Elementary School Science Learning course, as well as to analyze the need for implementing the Ethno-STEM Project-Based Learning (PjBL) model. The method used is descriptive qualitative, with data collection techniques in the form of questionnaires, interviews, and observations. The subjects of the study were 30 PGSD students and 2 lecturers teaching the Elementary School Science Learning course at one of the universities in Mataram City. The results of the study indicate that student creativity remains in the moderate category, and learning has not yet fully integrated local cultural values or project-based approaches. Students and lecturers welcome the idea of project-based learning, such as Ethno-STEM, as a solution to increase creativity. This study recommends the development of learning tools based on the Ethno-STEM PjBL model.